The `Great Moderation' in the United Kingdom - Luca Benati (European Central Bank (ECB), 2007)
We use a Bayesian time-varying parameters structural VAR with stochastic volatility for GDP deflator inflation, real GDP growth, a 3-month nominal rate, and the rate of growth of M4 to investigate the underlying causes of the Great Moderation in the United Kingdom. Our evidence points towards a dominant role played by shocks in fostering the more stable macroeconomic environment of the last two decades. Results from counterfactual simulations, in particular, show that (1) the Great Inflation was due, to a dominant extent, to large demand non-policy shocks, and to a lesser extent–especially in 1973 and 1979–to supply shocks; (2) imposing the 1970s' monetary rule over the entire sample period would have made almost no difference in terms of inflation and output growth outcomes; and (3)mechanically `bringing the Monetary Policy Committee vback in time' would only have had a limited impact on the Great Inflation episode, at the cost of lower output growth. These results are quite striking in the light of the more traditional, narrative approach, which suggests that the monetary policy regime is an important factor in explaining the Great Moderation in the United Kingdom. We discuss one interpretation which could explain both sets of results, based on the `indeterminacy hypothesis' advocated, for the United States, by Clarida, Gali, and Gertler (2000) and Lubik and Schorfheide (2004).
Keywords: E32; E47; E52; E58; 330; Bayesian VARs; European Monetary System; frequency domain; Great Inflation; identified VARs; Lucas Critique; policy counterfactuals; stochastic volatility; timevarying parameters; Konjunktur; Geldpolitik; Inflation; Neue klassische Makroökonomik; VAR-Modell; Bayes-Statistik; Großbritannien